Analisis Dampak Gaya Komunikasi Juru Bicara KPK Terhadap Persepsi Publik - Sigit Pramono Hadi (Inter Komunika, 2020)
Since its establishment in 2002, the Indonesian Corruption Eradication Commission (Komisi Pemberantasan Korupsi – KPK) has become the center of public attention in the context of combating corruption in Indonesia. In the area of KPK's legal action, they often carry out arrest operations against the perpetrators of corruption, which are followed by a press conference with the aim of explaining the cases of corruption that are allegedly committed to the perpetrators. At the press conference the prominent role of the KPK spokesman was seen as the official representative of the institution. Likewise on various occasions, the Spokesman spoke on behalf of the KPK to explain the corruption cases handled by the KPK. This study aims to measure the impact of the KPK spokesman's communication style on public perception in the context of eradicating corruption in Indonesia. By using a quantitative approach, this study aims to find out how the causality relationship between the independent variable (X) is the Communication Style with the dependent variable (Y), namely Public Perception. Respondents were selected using a non-probability sampling technique, namely accidental sampling. From the results of the study, it was found that the communication style of the KPK Spokesman had a positive impact on public perception and this positive impact had an influence strength of 15%. Thus an understanding that public perception about eradicating corruption in Indonesia is influenced by the communication style of the KPK spokesman by 15%. While the other 85% is determined by other variables not included in this study.